The Effect Of hCG (Human Chorionic Gonadotropin) Injection With Different Doses On Fertilitation, Hatching Rate and Survival Rate Of Fish Larvae Of Redfin Shark (Epalzeorhynchos frenatum) - Putri Utami; Sukendi Sukendi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe research was conducted from September to October 2018 in The Center for Research and Cultivivation of Ornamental Fish (BRBIH), Depok, West Java. The purpose of this research was to evaluate the effect of hCG to fertilization, hatching rate, and survival rate of larvae of redfin shark (Epalzeorhynchos frenatum) fish. The treatment used in this research was in injection of hCG with defferent doses is : P0: Control using NaCl 0,9% as much 0,2 ml/kg body weight, P1: Injection of hCG with dose 300 IU/kg body weight, P2: Injection of hCG with dose 500 IU/kg body weight, P3: Injection of hCG with dose 700 IU/kg body weight. The result showed that hCG dose of 500 IU/kg of body weight was the best in turn of fertilization 78,57%, hatching rate 86,02 %, and survival rate of larvae 93,96%.Keyword: hCG, Fertilization, Hatching Rate, Survival Rate, E. frenatum